+0  
 
0
152
4
avatar

1. f(x) = x2 - 4x + 5

2. f(x) = x2 + 3x + 4

3. f(x) = -x2 + 2x - 3

4. f(x) = -x2 - 5x - 9

5. f(x) = 3x2 - x + 2

Guest May 23, 2017
Sort: 

4+0 Answers

 #1
avatar+5589 
+1

On these, we want to solve for x when f(x) = 0

 

1.

0 = x2 - 4x + 5

 

We can solve this for x using the quadratic formula with

a = 1, b = -4, and c = 5

 

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a} \\~\\ x = {-(-4) \pm \sqrt{(-4)^2-4(1)(5)} \over 2(1)} ={4 \pm \sqrt{16-20} \over 2} ={4\pm\sqrt{-4}\over2} =\frac{4\pm2i}{2} \\~\\ x=2\pm i\)

__________________________________________________

 

2.

0 = x2 + 3x + 4

 

We can solve this for x using the quadratic formula with

a = 1, b = 3, and c = 4

 

Can you finish this one from here?

__________________________________________________

 

3.

0 = -x2 + 2x - 3

 

We can solve this for x using the quadratic formula with

a = -1, b = 2, and c = -3

 

\(x = {-2 \pm \sqrt{2^2-4(-1)(-3)} \over 2(-1)} = {-2 \pm \sqrt{4-12} \over -2} = {-2 \pm \sqrt{-8} \over -2} = \frac{-2\pm2i\sqrt2}{-2} \\~\\ x=1\pm i\sqrt2\)

__________________________________________________

 

4.

0 = -x2 - 5x - 9

 

We can solve this for x using the quadratic formula with

a = -1, b = -5, and c = -9

 

Can you finish this one from here?

__________________________________________________

 

5.

0 = 3x2 - x + 2

 

We can solve this for x using the quadratic formula with

a = 3, b = -1, and c = 2

 

\(x = {-(-1) \pm \sqrt{(-1)^2-4(3)(2)} \over 2(3)} ={1 \pm \sqrt{-23} \over 6} \\~\\ x={1 \pm i\sqrt{23} \over 6}\)

hectictar  May 23, 2017
edited by hectictar  May 23, 2017
 #2
avatar+1493 
+1

 

 

Finding the zeros of a function simply means to set the domain equal to zero and then solve. 

 

1. Let's do the first together:

 

\(x^2-4x+5=0\)

 

This equation is not factorable, so we have to use a different method other than factoring. Let's use the quadratic equation:

 

\(x = {-b\pm \sqrt{b^2-4ac} \over 2a}\)

 

a=1, b=-4, c=5

 

\(x = {-(-4) \pm \sqrt{(-4)^2-4(1)(5)} \over 2(1)}\)

 

Let's simplify this. First, I'll simplify what it is in the radical:
 

\(x = {4 \pm \sqrt{16-20} \over 2}\)

\(x = {4\pm2i\over 2}=2\pm i\)

 

The solution is 2+/- i.

2. Let's do the second one. Here is the original equation:

 

\(x^2+3x+4=0\)

 

This one, too, cannot be factored. I'll use the quadratic equation again:

 

\(x = {-3 \pm \sqrt{3^2-4(1)(4)} \over 2(1)}\)

 

I have simply substituted all the values into the equation. Now, solve for x:

 

\(x = {-3 \pm \sqrt{9-16} \over 2}\)

\(x = {-3 \pm \sqrt{-7} \over 2}\)

\(x = {-3\pm i\sqrt{7} \over2}\)

3. Here's the original equation:
 

\(-x^2+2x-3=0\)

 

I'll use the quadratic formula for the third time:

 

\(x = {-2 \pm \sqrt{2^2-4(-1)(-3)} \over 2(-1)}\)

\(x = {-2 \pm \sqrt{4-12} \over -2}\)

\(x = {-2\pm \sqrt{-8} \over -2}\)

\(x = {-2 \pm 2i\sqrt{2} \over -2}=1\pm i\sqrt{2}\)

 

4. Here's the original equation:

 

\(-x^2- 5x - 9=0\)

 

This is not factorable, so we must use the quadratic formula again. 

 

\(x = {5\pm \sqrt{-11} \over-2}\)

 

\(x = {-5 \pm i\sqrt{11} \over2}\)

 

5. This one is the same story as the previous ones:

 

\(x = {1\pm\sqrt{-23} \over6}\)

\(x=\frac{1\pm i\sqrt{23}}{6}\)

TheXSquaredFactor  May 23, 2017
edited by TheXSquaredFactor  May 23, 2017
 #3
avatar+79894 
+2

 

Whoa....hold on a minute, X^2.....These definitely have solutions.....!!!

 

They are not  real solutions, but they are solutions, nonetheless..........

 

 

 

cool cool cool

CPhill  May 23, 2017
 #4
avatar+1493 
0

Fine... you win...

 

Fixed for your liking!

TheXSquaredFactor  May 23, 2017
edited by TheXSquaredFactor  May 23, 2017

9 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details